Assessment of Nurse Perspectives on an Emergency Department‐Based Routine Opt‐Out HIV Screening Program. (May 2017) - Heinert, Sara; Carter, Julius; Mauntel‐Medici, Cammeo; Lin, Janet
Abstract : N/A: Routine opt‐out HIV screening is recommended for everyone between 13 and 64 years of age. An urban, academic emergency department implemented a nurse‐driven routine opt‐out HIV screening program. The aim of our study was to assess program uptake and opportunities to improve the program from the perspectives of emergency nurses. Emergency nurses completed a brief prediscussion questionnaire and then participated in a focus group or semi‐structured one‐on‐one interview to elicit feedback on the routine opt‐out HIV screening program. All 16 participants felt adequately prepared for the screening program. Several themes emerged from the discussions, including challenges of specific patient characteristics and overall nurse and patient support for the program. One thread across themes was the importance of good language and communication skills in such programs. While there are opportunities to improve nurse‐driven routine opt‐out HIV testing programs in emergency settings, this program was found to be accepted by emergency nurses.